The Effect of Cognitive Stimulation on Cognition and Depressive Symptomatology in Elderly Community - Apóstolo, João Luís Alves (2015)
Apóstolo, João L. A; Almeida, Maria; Cardoso, Daniela.Dwellers,43rd ,Las Vegas, Nevada,2015